Bimodal radiotherapy with active raster-scanning carbon ion radiotherapy and intensity-modulated radiotherapy in high-risk nasopharyngeal carcinoma results in excellent local control - Akbaba, Sati; Held, Thomas; Uzun-Lang, Kristin; Forster, Tobias; Federspil, Philippe A.; Herfarth, Klaus; Häfner, Matthias; Plinkert, Peter K.; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Cancers, 2019)
Background: In this analysis, we aimed to present the first results of carbon ion radiotherapy (CIRT), which is known for its conformal dose distribution and increased biological effectiveness in the treatment of high-risk nasopharyngeal carcinoma (NPC). Methods: We retrospectively analyzed twenty-six consecutive patients who had been treated at our center with CIRT for high-risk NPC between 2009 and 2018. Carbon ion (C12) boost was applied in a bimodal setting combined with intensity-modulated radiotherapy (IMRT) base plan. The median cumulative total dose was 74 Gy (RBE), and patients with inoperable (n = 17, 65%) or incompletely resected (n = 7, 27%) tumors were included in the analysis. Overall, 81% received concomitant chemotherapy (n = 21). Results: The median follow-up time was 40 months (range 10–97 months) for all patients. At the last follow-up, 92% of the patients were still alive. We could identify excellent tumor response with complete tumor remission (CR) in 60% (n = 15/25), partial tumor remission (PR) in 20% (n = 5/25), and stable disease (SD) in 12% (n = 3/25) of the patients according to the RECIST (Response Evaluation Criteria in Solid Tumors) criteria. Despite unfavorable tumor characteristics, only one patient showed a locally in-field recurrence after 56 months (4%) and another patient a locoregional recurrence in the unilateral cervical lymph nodes after 21 months (4%). The 2-year local control (LC), distant progression-free survival (DPFS), and overall survival (OS) were 95%, 93%, and 100% and the estimated 5-year LC, DPFS, and OS were 90%, 86%, and 86%, respectively. Overall, treatment was tolerated well with 20% acute and 16% chronic grade 3 side effects. No toxicity greater than grade 3 occurred. Conclusion: Bimodal radiotherapy including IMRT and active raster-scanning CIRT for high-risk nasopharyngeal cancer is a safe treatment method resulting in moderate toxicity and excellent local control. A larger patient number and longer follow-up time would be necessary to strengthen the current findings.
Gesehen am 10.04.2019